Near field localization of moving sources with REM algorithms - (:unkn) unknown (My University, 2009)
0

In this paper, we present the problem of joint tracking of the direction of arrival (DOA) and range parameters of moving sources in the near field of an antenna array with two Expectation- Maximization (EM) based recursive algorithms. The main characteristic of the first Recursive EM (REM) approach is to include computation of the gradient of the log-likelihood function and some form of the complete data Fisher information matrix. Compared to first REM approach, the second one utilizes the stochastic approximation of approximate conditional expectation of the complete data sufficient statistics. The proposed recursive algorithms in this work assume that the parameters of interest are described by a linear polynomial model. This paper concludes by presenting the simulation results of the suggested algorithms in order to illustrate the computational effectiveness of the both algorithms.
Keywords: Mühendislik, Elektrik ve Elektronik